Retrospective Study of Prevalence and Pattern of Surgical Conditions Presented at the Ashanti Regional Veterinary Clinic, Kumasi, Ghana (2014)
Case records of animal patients presented for surgery at the Ashanti regional veterinary clinic, Kumasi, Ghana, within a seven year (1997-2013) period were studied for surgical disease prevalence and pattern among animal species. The age, sex and breeds, as well as, quarterly distribution of surgical cases were also evaluated. A gradual increase in numbers and types of surgical conditions were observed across the years studied, with the least prevalence in 2007 (2.6%) and the highest in 2013 (29.2%).Wounds /trauma cases were highest (41.0%) and vaginal prolapse least (0.1%) among surgical cases managed. Most surgical conditions were in canine species (96.0%), while the rest (3.8%) were in feline (2.4%), equine (0.5%), caprine (0.4%) and ovine (0.4%) species. Among the twenty–one dog breeds presented for surgical management, the local breed (mongrel) had the highest occurrence (40.2%) of surgical conditions, while the poodle (0.1%), Daschund (0.1%) and Labrador (0.1%) had the least. Male dogs (57%) were presented more for surgery than females (35%). Also, younger dogs (57%) had more surgeries than adult dogs (35%). Most surgical cases were presented in the fourth quarter (October–December) (31.4%) and the least in the second quarter (April –June) (18.5%). The implications of the data to regional, national and global planning and training of Veterinarians on animal surgical disease management were discussed